La situación internacional y la política exterior de China - Zhaorong, Mei (Revista Mexicana de Política Exterior, 2022)
This work presents the comments of specialists on the changes in the international strategic configuration after the fall of the Berlin Wall. It deals with topics such as moving from a bipolar world to a situation of one superpower coexisting with other countries with less power. It studies the impact of economic globalization, a multi-polar trend. The essay discusses China’s position towards the current international panorama and its proposals regarding terrorism and the conflict in Afghanistan. The author emphasizes the basic principles and objectives of China’s foreign policy.